Serviço Social Audit Saúde no SUS/RN: projeto ético político profissional e de reforma sanitária - Medeiros, Aparecida Dantas de Almeida (2011)
Health policies in Brazil, the decentralization of SUS management responsibilities for the three spheres of government has driven the creation and regulation of the audits of health services in the National Audit Office, this is a trend of neoliberal policies imposed by international bodies like the World Bank and IMF to peripheral countries characterized by productive restructuring and reforming the state focuses on the presence of two competing projects in the area of health: Health Sector Reform Project which is based on the democratic rule of law with the assumption of health as social right and duty of the State in defending the extension of the conquest of rights and democratization of access to health care guaranteed through the public financing strategies and the effective decentralization of decisions pervaded by social control and privatized Health Project which is based on the state minimum, with a reduction in social spending or in partnerships and privatization, stronger nonprofit sector, subject to capitalist interests, is made effective through strategies targeting health policy and refilantropização actions. In this context, the present study is an analysis on the work of social audits of public health in infants from a qualitative and quantitative approach, embodied by the critical method of dialectical Marxist social theory that enabled us to unveil the characterization, the demands, challenges and outline the profile of Social Work in teams inserted audits of SUS in RN, but also provided evidence to demonstrate the prospects and possibilities of this area of activity of social workers. It was also found that through the audit work that the state fulfill its role as bureaucratic and regulator of health services with efficiency, effectiveness and economy. Yet, paradoxically, the audits of SUS may provide a vehicle for enforcing rights and ensuring the fundamental principles contained in the project of health reform, because it can be configured in a space of political struggle as representing a new field of knowledge production that needs to be appropriate for a theoretical critic able to redirect the social interests in favor of the user. From this perspective, it is concluded that the work of social audits of public health in infants despite the social relevance that prints, as they constitute an activity study of reality and its transformation proposition requires a transformative political action guided the discussion Marxist theory holds that the ethical project professional politician of Social Work